Cochlear implantation in children with white matter lesions: Prediction of hearing outcomes by multiple regression analysis. Issue 1 (8th January 2021) - Wang, Sufang; Wang, Yannan; Li, Yongxin; Wei, Yanyan; Han, Fugen; Ren, Hongbo; Xu, Ying; Cui, Yanhong
Abstract : Abstract: Brain magnetic resonance imaging (MRI) white matter lesions have been reported in some preoperative cochlear implant children. However, the role of white matter lesions in predicting the hearing outcome is yet unclear. The present study investigated the outcomes of cochlear implantation (CI) in 40 children with white matter lesions. The data from children with white matter lesions were reviewed in this retrospective study. Based on brain MRI, the patients were divided into 3 groups: mild, moderate, and severe. The children were treated with unilateral CI and monitored for a follow-up period of at least 3 years. The main outcome measures were category of auditory performance (CAP) and speech intelligibility rating (SIR). MRI white matter lesions, age at implant, gender, physical impairment, and cognitive impairment were obtained from a research database to assess the correlation with long-term CAP and SIR outcome by multiple regression analysis. The data of children with white matter lesions were reviewed (18 females and 23 males). The mean age at implantation was 31.6 months. Strikingly, all children obtained better CAP and SIR scores. The age at implantation, brain white matters lesions on MRI, and cognitive and physical disabilities were associated with CAP and SIR scores. Multiple regression established a weak correlation between the degree of white matter lesions on brain MRI and long-term CAP and SIR, while cognitive impairment strongly accounted for long-term CAP and SIR outcome. The majority of the children with brain white matter lesions obtained a satisfactory postoperative effect. The cognitive impairment before CI is a major factor, and such factor should be considered.